Effects of stocking density on growth and production of shing (Heteropneustes fossilis) in ponds (Asian-Australasian Journal of Bioscience and Biotechnology, 2016)
To assess the effects of stocking density on growth and production of shing (Heteropneustes fossilis)in ponds, an experiment was carried out for a period from 06 August to 22 December, 2015. Three stocking densities used were 80, 160 and 240 fish /decimal and designated as T1, T2 and T3, respectively. Each treatment has two replications. Shing having a mean body weight of 1.18g was used in T1, T2 and T3, respectively. A commercial feed fed at the rate of 50% of body weight up to first 15 days and then gradually it was readjusted to 35%, 25%, 15%, 5% and 2% respectively. The water quality parameters were monitored at 15 days interval and the ranges were: temperature 23.0 ºC to 30.25 ºC, pH 6.64 to 8.16, dissolved oxygen 4.91 to 6.99 mg/l and transparency 36.15 to 41.5 cm. Results showed that, the fish stocked at the rate of 80 fish/decimal in T1  get best individual weight gain (42.63g) followed by T2(38.52g) and T3 (34.82g), respectively. The SGR ranged between (1.77to1.81) %/day. There was significant variation (P